Development and application of a questionnaire to self-rate physical work demands for ground combat soldiers. (February 2020) - Larsson, Jonas; Dencker, Magnus; Olsson, M. Charlotte; Bremander, Ann
Abstract: Purpose: The aim of the present study was to identify the most physically demanding work tasks for Swedish ground combat soldiers through the development and application of a questionnaire survey. This is the first in a series of studies aiming to describe the development process and validation of physical selection standards in the Swedish armed forces. Methods: Based on procedural documentation, combat manuals and job analyses, a questionnaire was developed that defined and rated the perceived physical strain of 30 work tasks for ground combat soldiers. To assess validity, an expert focus group was used and psychometric analysis performed. The questionnaire was then distributed to 231 ground combat soldiers, of whom 165 responded (71%). Results: The questionnaire was validated in three steps to achieve face and content validity, and internal consistency was acceptable (Chronbach's alpha ≥0.95). Of the 30 work tasks included in the survey, transport of wounded was rated as the most demanding task for both aerobic capacity and strength. Other highly demanding tasks for aerobic capacity included combat movement (low/high crawl), dismounted attack in close country, urban and rough terrain and carrying heavy loads. There were no gender differences for either aerobic or strength demands in the top five most challenging tasks based on proportions. Conclusions: This study identified the most physically demanding tasks performed in the Swedish ground combat forces. Almost all the physically demanding tasks found in the present study contain elements of lifting and carrying, which require muscular strength and muscular endurance, with no gender differences. Highlights: Transport of wounded soldier most demanding both for aerobic capacity and strength demands. No significant difference was found between male and female soldiers although they sometime ranked task in different order. The result shows that the process and methodology with a questionnaire can be used to identify the most demanding task. Validity is an ongoing process why more studies are needed to assess full validity and reliability of the questionnaire. Almost all the tasks in the study consisted lifting and carrying tasks, demanding strength and endurance capabilities.